E-041 Subacute endovascular recanalization of supraclinoid internal carotid artery occlusions. (4th July 2012) - Vranic, J; Grobelny, T; Hurley, M; Shaibani, A; Bendok, B; Batjer, H; Ansari, S
Abstract : Purpose: Managing subacute or chronic cervical/intracranial thromboembolic occlusions can be challenging. With respect to the COSS trial, when medical treatment fails and ischemic symptoms persists, surgical bypass procedures may be considered to preserve neuronal survival and function. We report on two cases involving the rare endovascular recanalization of subacute supraclinoid ICA occlusions via mechanical thrombectomy, and discuss its feasibility and potential risks. Case 1/image findings: 20-year-old male presented with transient aphasia and right-sided hemiplegia. CT/MR/DSA imaging identified a left temporal lobe infarct and supraclinoid LICA occlusion, but with collateral flow across the Acomm supplying the left ACA and MCA. 1-week later, the patient represented with transient right-sided weakness/numbness and facial droop and new DWI infarcts in the left corona radiata and left insular cortex. Repeat DSA showed thrombus progression into the carotid terminus restricting flow across the Acomm into the left MCA distribution, now dependent on pial collaterals. 2-weeks later, the patient was transferred to our institution for surgical bypass procedure on heparin anticoagulation and hemodynamic augmentation. Gross CBF abnormality and progression of "silent" left MCA infarcts were noted on repeat MR PWI/DWI. In preparation for STA-MCA bypass, normotensive challenge was attempted, but a hemiparetic/aphasic state ensued not responsive to hemodynamic augmentation. Emergent endovascular recanalization via probing the thromboembolic occlusion with the Penumbra vacuum aspiration thrombectomy device and adjunctive 10 mg tPA, resulted in TICI 2b antegrade reperfusion of the left ACA/MCA. Post-procedure, the patient was hemodynamically relaxed to normotension without any neurological deficits and continued on heparin anticoagulation followed by antiplatelet therapy. Follow-up CT and MRI/MR PWI demonstrated significantly improved CBF in both left ACA/MCA distributions, but asymptomatic complications of distal iatrogenic emboli and mild petechial/perisylvian SAH conversion were noted and managed by intermittently terminating anticoagulation/antiplatelet therapy without incident. Case 2/image findings: 58-year-old male with history of hypertension, hyperlipidemia, and smoking/alcohol presented with left facial droop, left arm weakness. MRI/MRA identified multifocal watershed infarcts secondary to RICA occlusion. Six days later, the patient developed worsening hemiparesis despite hemodynamic augmentation and antiplatelets. DSA confirmed supraclinoid RICA occlusion with delayed collateral flow across the Acomm due to a hypoplastic R A1 segment. Intracranial balloon angioplasty was successful in establishing TICI 3 reperfusion to the right cerebral hemisphere. Both patients made remarkable recoveries without residual neurological deficits or dependency on hemodynamic augmentation. Summary: Endovascular recanalization of subacute, intracranial thromboembolic occlusions is feasible and may represent an alternative strategy when patients' neurological and hematological status cannot tolerate a surgical bypass procedure. Since significant risk for complications exist including distal iatrogenic emboli, reocclusion, reperfusion hemorrhage, and hemorrhagic conversion of subacute infarcts, it should be reserved until multidisciplinary consultation documents failure of optimum medical management, recurring TIAs/strokes, severe regional hypoperfusion or ischemia dependent on hemodynamic augmentation. In addition, vigilant attention to post-procedure management is crucial in limiting complications by titrating hemodynamic control, anticoagulation and especially antiplatelet medications if stenting is performed. Competing interests: None.